The Influence of Postal Mediater towards Interest in Learning Natural Science Subjects Class V Madrasah Ibtidaiyah Muhammadiyah Kemusu Boyolali - Siti Aminah; Iffah Mukhlisah; Sugiyat (CV. Creative Tugu Pena, 2024)
This study aims to 1) Knowing the level of use of poster media in Natural Science subjects for grade V students at Madrasah Ibtidaiyah Muhammadiyah Kemusu, Boyolali Regency in 2023/2024, 2) Knowing the level of interest in learning in Natural Science subjects of grade V students at Madrasah Ibtidaiyah Muhammadiyah Kemusu, Boyolali Regency in 2023/2024, 3) Knowing how much infulence poster media has on interest in learning Natural Science subjects of grade V students at Madrasah Ibtidaiyah Muhammadiyah Kemusu, Boyolali Regency in 2023/2024. The approach taken in this research is a quantitative approach, with the type of research being a correlation type. The research was conducted at Madrasah Ibtidaiyah Muhammadiyah Kemusu, Boyolali Regency. Data collection was carried out with a questionnaire by testing use this research is descriptive statistics. To test the validity of the data, a prerequisite test with normality test and linearity test was conducted; and hypothesis testing using partial test (t test) and determination coefficient test. The results of this study indicate that: 1) the level of poster media is in the high category as evidenced by the presence of 12 students from 30 samples showing the largest persentage of 40%. 2) the level of interest in learning is in the high category, out of 30 samples 12 students show a percentage of 40%, 3) the magnitude of the influence of poster media on interest in learning Natural Science subjects is known by the results of the calculation of the coefficient of determination, which is 65.1% and the remaining other variables that are not studied are 34.9%.